SIKLUS KONVERSI KAS: ALTERNATIF RASIO LIKUIDITAS YANG LEBIH BAIK DALAM MEMPREDIKSI PROFITABILITAS - Muh Juan Suam Toro; Deny Dwi Hartomo (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2014)
The aim of this research are to investigate the effect of cash conversion cycle on firm profitability and to compare that effect to the effect of classic liquidity ratio on firm profitability. This research is also to investigate the effect of cash conversion cycle on firm firm profitability in different firm sizes and industries. The population of research object is companies listed on Indonesian Stock Exchange from 2006 to 2009. Sampling method used is purposive sampling. Samples consist of member of Manufacture industry represented by Plastic and Glass sub-industry and member of Service industry represented by Transportation Service sub-industry. The statistic tool used is multiple regression. The result shows that the cash conversion cycle has negative effect on firm profitability. There is no difference effect between different industry and firm size. Keywords: cash conversion cycle, firm profitability,industry, firm size